The site characterization of central jakarta soft soil using CPTu and laboratory test - Andrianto Muliawan Permana; Paulus Pramono Rahardjo (Indonesian Geotechnical Journal, 2022)
Construction activities has been named as one of the contributing factors to Jakarta’s alarming rate of land subsidence, which ranges between 1 to 15 cm annually, and up to 28 cm in some locations. This problem is commonly known as settlement, and the affected soft soil is usually attributed to under-consolidating soil (UC). In regards to that matter, this study aims to characterize the soft soil layer in Central Jakarta using the Cone Penetration Test with pore pressure measurement (CPTu) and laboratory assessment. In addition, Undrained Shear Strength () and Pore Pressure Ratio (and ) methods were used to estimate the over-consolidation Ratio (OCR) values. The data collected from 94 boreholes and 30 CPTu showed the soft soil layers in Central Jakarta, which was dominated by high-plasticity silty clay (CH) and clayey silt (MH). The layers are detected between the depth of 0 – 25 m and are characterized by high natural moisture content, void ratio, liquidity index, and compression index values. Within this layer of under consolidated soils, the indication of relatively low dry unit weight was also present. Furthermore, the laboratory tests showed several correlations related to under-consolidating soil, i.e. void ratio to in-situ effective stress, void ratio to compression index, and compression index to natural moisture content. The CPTu test interpretations returned a number of under-consolidation soil layer samples in Central Jakarta. Moreover, the result also indicates the presence of under-consolidating properties, as well as normally consolidated and lightly over-consolidated.